Analysis and Design of Networked Control Systems with Random Markovian Delays and Uncertain Transition Probabilities - Li Qiu; Chengxiang Liu; Fengqi Yao; Gang Xu (Abstract and Applied Analysis)
This paper focuses on the stability issue of discrete-time networked control systems with random Markovian delays and uncertain transition probabilities, wherein the random time delays exist in the sensor-to-controller and controller-to-actuator. The resulting closed-loop system is modeled as a discrete-time Markovian delays system governed by two Markov chains. Using Lyapunov stability theory, a result is established on the Markovian structure and ensured that the closed-loop system is stochastically stable. A simulation example illustrates the validity and feasibility of the results.